Articulation Problems between the Balance Sheet and the Funds Statement - Maksy, Mostafa M. (The Accounting Review, 1988)
[This Small Sample Study describes and illustrates two types of discrepancies that can occur between the change in certain balance sheet amounts as derived from comparative balance sheets and the change that is reported in the funds statement. Four possible causes for such discrepancies are discussed and disclosure policies that would help to overcome some possibly serious reporting deficiencies are suggested.]